2023
DOI: 10.1097/md.0000000000032629
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride-glucose index and contrast-induced nephropathy in non-ST elevation myocardial infarction patients undergoing percutaneous coronary intervention

Abstract: The triglyceride glucose (TyG) index is an indicator of insulin resistance and associated with increased risk of diabetes mellitus and cardiovascular events. Our study investigates the correlation between TyG index and contrast induced nephropathy (CIN) in non-diabetic patients with non-ST elevation myocardial infarction (NSTEMI) undergoing percutaneous coronary intervention (PCI). 350 non-diabetic NSTEMI patients (183, 52.3% male) undergoing PCI were retrospectively enrolled. The enrolled cohort was divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The “metabolic comorbidity problem” can significantly affect the prognosis of PCI and is also a treatment difficulty, making it a research hotspot. [ 25 ] TCM provides a systematic diagnosis and treatment of coronary heart disease. In recent years, evidence-based medicine has been continuously developed, and research has shown that TCM and other factors can affect the prognosis of PCI.…”
Section: Discussionmentioning
confidence: 99%
“…The “metabolic comorbidity problem” can significantly affect the prognosis of PCI and is also a treatment difficulty, making it a research hotspot. [ 25 ] TCM provides a systematic diagnosis and treatment of coronary heart disease. In recent years, evidence-based medicine has been continuously developed, and research has shown that TCM and other factors can affect the prognosis of PCI.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 350 patients without diabetes who were undergoing PCI for acute coronary syndrome, Gursoy and Baydar observed that the incidence of CIN was significantly higher in those with high TyG indices (≥8.65) than in those with lower indices (<8.65) (14). Importantly, the predictive value of the TyG index for CIN appears to be present even after adjusting for potential confounders such as diabetes status (13,14). While promising, research on the TyG index and CIN risk remains limited.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have suggested that the TyG index could serve as a predictive marker for cardiovascular risk such as coronary artery disease, heart attack, and stroke (9,10,12). In addition, some studies have explored the potential connection between the TyG index and nephropathy, particularly in diabetic nephropathy (13)(14)(15)(16)(17). A higher TyG index, indicative of insulin resistance, can contribute to inflammation, oxidative stress, and vascular dysfunction (9,15,18).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations